A qualitative study: beliefs and attitudes of women undergoing abdominal hysterectomy in Turkey. Issue 5 (1st August 2008) - Reis, N.; Engin, R.; Ingec, M.; Bag, B.
Abstract : The study was designed as a descriptive one to reveal the beliefs and attitudes of the women undergoing abdominal hysterectomy. It was carried out at the university hospital in Erzurum between July 2005 and March 2006. The data were collected through semistructured in-depth interviews with 31 women undergoing abdominal hysterectomy. The data obtained were evaluated by content analysis. These evaluations revealed five themes concerning the beliefs and attitudes of the women undergoing abdominal hysterectomy: (1) feminine identity, (2) husband/family relationships, (3) sexual life, (4) menopause, and (5) relatives' opinions. These findings about cultural beliefs and attitudes of the women undergoing hysterectomy will enable health care providers to provide culturally sensitive and comprehensive care to women; it is also expected to enable health care providers to instruct women to avoid unnecessary delay of hysterectomy